Iranian Obese Women's Lived Experiences of Social and Linguistic Factors Shaping Emotional Eating Behavior: A Phenomenological Study - Ehteram Ebrahimi; Fatemeh Mohammadi Shirmahaleh; Marjan Mardani Hamooleh; Mojtaba Habibi Asgarabad (Kerman University of Medical Sciences, 2023)
Background: Emotional eating is harmful to health and is highly prevalent in obese women. Hence, an awareness of factors underlying emotional eating is important for weight management and maintaining women's health. Research evidence indicates that several factors contribute to emotional eating behavior. The present study aimed to explore obese young Iranian women's lived experiences of social and linguistic factors shaping emotional eating behavior.Methods: This qualitative and hermeneutic phenomenological study was conducted on 17 young women living in Kermanshah or Karaj, Iran who experienced emotional eating and had a body mass index (BMI) of 30 and higher. The participants were selected using purposive sampling with maximum variation in terms of demographic characteristics. The data were collected through in-depth individual and face-to-face interviews and analyzed using Dickelman et al's seven-step phenomenological approach.Results: The data analysis revealed that social and linguistic factors underlying emotional eating behavior can be explained by two themes including social influence and linguistic culture. Social influence further accounted for compensating for the stigma of thinness, relieving the stigma of obesity, group conformity, and following taboos to cope with sexual and emotional desires. In addition, linguistic culture was explained by two subthemes including associating grieving with eating and the metaphor of swallowing anger.Conclusion: Following the findings of the study, psychotherapy interventions can be planned to address emotional eating and weight management with a focus on the role of social influence and the effects of spoken language in the development of emotional eating behavior.